When Aortic Stenosis Is Not Alone: Epidemiology, Pathophysiology, Diagnosis and Management in Mixed and Combined Valvular Disease - Mantovani, Francesca; Fanti, Diego; Tafciu, Elvin; Fezzi, Simone; Setti, Martina; Rossi, Andrea; Ribichini, Flavio; Benfari, Giovanni (Frontiers in Cardiovascular Medicine, 2021)
Aortic stenosis (AS) may present frequently combined with other valvular diseases or mixed with aortic regurgitation, with peculiar physio-pathological and clinical implications. The hemodynamic interactions between AS in mixed or combined valve disease depend on the specific combination of valve lesions and may result in diagnostic pitfalls at echocardiography; other imaging modalities may be helpful. Indeed, diagnosis is challenging because several echocardiographic methods commonly used to assess stenosis or regurgitation have been validated only in patients with the single-valve disease. Moreover, in the developed world, patients with multiple valve diseases tend to be older and more fragile over time; also, when more than one valvular lesion needs to address the surgical risk rises together with the long-term risk of morbidity and mortality associated with multiple valve prostheses, and the likelihood and risk of reoperation. Therefore, when AS presents mixed or combined valve disease, the heart valve team must integrate various parameters into the diagnosis and management strategy, including suitability for single or multiple transcatheter valve procedures. This review aims to summarize the most critical pathophysiological mechanisms underlying AS when associated with mitral regurgitation, mitral stenosis, aortic regurgitation, and tricuspid regurgitation. We will focus on echocardiography, clinical implications, and the most important treatment strategies.